Facilitation of ischaemia‐induced ventricular fibrillation by catecholamines is mediated by β1 and β2 agonism in the rat heart in vitro. (2nd April 2018) - Wilder, Catherine D E; Pavlaki, Nikoleta; Dursun, Tutku; Gyimah, Paul; Caldwell‐Dunn, Ellice; Ranieri, Antonella; Lewis, Hannah R; Curtis, Michael J
Abstract : Background and Purpose: Antiarrhythmic β‐blockers are used in patients at risk of myocardial ischaemia, but the survival benefit and mechanisms are unclear. We hypothesized that β‐blockers do not prevent ventricular fibrillation (VF) but instead inhibit the ability of catecholamines to facilitate ischaemia‐induced VF, limiting the scope of their usefulness. Experimental Approach: ECGs were analysed from ischaemic Langendorff‐perfused rat hearts perfused with adrenoceptor antagonists and/or exogenous catecholamines (CATs: 313 nM noradrenaline + 75 nM adrenaline) in a blinded and randomized study. Ischaemic zone (IZ) size was deliberately made small or large. Key Results: In rat hearts with large IZs, ischaemia‐induced VF incidence was high in controls. Atenolol, butoxamine and trimazosin did not affect VF at concentrations with β1 ‐, β2 ‐ or α1 ‐ adrenoceptor specificity and selectivity (confirmed in separate rat aortae myography experiments). In hearts with small IZs and low baseline incidence of ischaemia‐induced VF, CATs, delivered to the uninvolved zone (UZ), increased ischaemia‐induced VF incidence. This effect was not mimicked by atrial pacing, hence, not due to sinus tachycardia. However, the CATs‐facilitated increase in ischaemia‐induced VF was inhibited by atenolol and butoxamine (but not trimazosin), indicative of β1 ‐ and β2 ‐ but not α1 ‐adrenoceptor involvement (confirmed by immunoblot analysis of downstream phosphoproteins). CATs did not facilitate VF in low‐flow globally ischaemic hearts, which have no UZ. Conclusions and Implications: Catecholamines facilitated ischaemia‐induced VF when risk was low, acting via β1 ‐ and β2 ‐ adrenoceptors located in the UZ. There was no scope for facilitation when VF risk was high (large IZ), which may explain why β‐blockers have equivocal effectiveness in humans.